T Cell Fate at the Single-Cell Level - Buchholz, Veit R; Schumacher, Ton N M; Busch, Dirk H (Annual review of immunology, 2016)
T cell responses display two key characteristics. First, a small population of epitope-specific naive T cells expands by several orders of magnitude. Second, the T cells within this proliferating population take on diverse functional and phenotypic properties that determine their ability to exert effector functions and contribute to T cell memory. Recent technological advances in lineage tracing allow us for the first time to study these processes in vivo at single-cell resolution. Here, we summarize resulting data demonstrating that although epitope-specific T cell responses are reproducibly similar at the population level, expansion potential and diversification patterns of the offspring derived from individual T cells are highly variable during both primary and recall immune responses. In spite of this stochastic response variation, individual memory T cells can serve as adult stem cells that provide robust regeneration of an epitope-specific tissue through population averaging. We discuss the relevance of these findings for T cell memory formation and clinical immunotherapy.